1991
DOI: 10.1021/bi00100a004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of mutagenesis by exocyclic DNA adducts. Transfection of M13 viral DNA bearing a site-specific adduct shows that ethenocytosine is a highly efficient RecA-independent mutagenic noninstructional lesion

Abstract: It is widely accepted that mutagenic DNA lesions fall into two categories: mispairing lesions hydrogen bond with an incorrect incoming base, generally do not stop replication, and possess high mutagenic efficiency without any requirement for induced functions; noninstructional lesions lack accessible template information, act as strong blocks to DNA replication (and are therefore toxic), and their mutagenic effects are SOS-dependent. Our recent results show that ethenocytosine (epsilon C), a noninstructional e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
75
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 33 publications
10
75
1
Order By: Relevance
“…εC•T or εC•A were the main mispairs when E. coli polymerases were used (36)(37)(38). A later study using M13 viral DNA showed that 30% of progeny phage obtained by transfecting εC-DNA had a base substitution mutation at the lesion site (39). In agreement with the first reports, all these mutations were either C → T transitions or C → A transversions.…”
Section: Discussionsupporting
confidence: 83%
“…εC•T or εC•A were the main mispairs when E. coli polymerases were used (36)(37)(38). A later study using M13 viral DNA showed that 30% of progeny phage obtained by transfecting εC-DNA had a base substitution mutation at the lesion site (39). In agreement with the first reports, all these mutations were either C → T transitions or C → A transversions.…”
Section: Discussionsupporting
confidence: 83%
“…Because of the etheno bridging of two of the three hydrogen-bonding positions, εC is expected to be a noninstructive lesion. The in vitro (56) and in vivo (27,28,49) template characteristics of εC are indeed those expected for such a lesion. For example, none of the four nucleotides are inserted by E. coli DNA pol I Klenow fragment opposite a site-specific εC residue borne on an oligodeoxyribonucleotide template under conditions in which guanine insertion opposite normal cytosine can be readily demonstrated on a control template (56).…”
supporting
confidence: 58%
“…Because of the etheno bridging of two of the three hydrogen-bonding positions, εC is expected to be a noninstructive lesion. The in vitro (56) and in vivo (27,28,49) template characteristics of εC …”
mentioning
confidence: 99%
“…Ethenocytosine in site-directed mutagenesis experiments in E. coli and mammalian cells gave rise to 1.5 or 2% of targeted mutagenic events in non SOS-induced E. coli cells [55,58], 30% in SOS-induced ones, and 81% in simian kidney cells [58,59]. The predominant mutations generated by εC in both E. coli and COS cells were C:G → A:T transversions and C:G → T:A transitions.…”
Section: Translesion Synthesis Of Exocyclic-dna Adducts and Their Mutmentioning
confidence: 99%